PERAN LABORATORIUM PEMASARAN DALAM MENUNJANG KESIAPAN SISWA MELAKSANAKAN PRAKTIK KERJA LAPANGAN - Amalia Sari; Sri Wahyuni; Leny Noviani (BISE: Jurnal Pendidikan Bisnis dan Ekonomi, 2017)
The research purpose is to explore (1) the implementation of practical activities in the Marketing Laboratory; (2) the Marketing Laboratory roles; (3) the constraints; (4) the efforts. This research using a single case study, qualitative research approach with the result: First, the practice were conducted in the second grade with material which according to curriculum and the needs of DU / DI. The guidance process was done three times a day. The practice evaluation including the aspect of capabilities, personalities and attitudes. Second, there are two of roles marketing laboratory, they are as a tool of supporting the learning process which not maximally because of the infrastructure is unqualified and as a training tool in improving students' skill. Third, the constraint faced by students including the adjustment, the use of facilities and application, dealing with customers, the student attitude which less of attention, urbane, confident, alert, many questions and apathy so they just are waiting for order. Fourth, the school efforts are: evaluates and follow up on feedback from DU/DI, provide counseling and debriefing before the implementation of the field work practice, give opportunity for students to express the process and the constraint of field work practice.